Implementasi Program Kartu Indonesia Sehat di Desa Lubuk Saban Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Hairida Wati; Indra Muda; Irwan Nasution (Universitas Medan Area, 2023)
The The healthy Indonesian card is a card that has a function to provid health insurance to the underprivileged with the aim of getting free health services in order to make it easier for the underprivileged in treatment. The purpose of this study was to determine the implementation of the Healthy Indonesia Card program in Lubuk Saban Village, Pantai Cermin District, Serdang Bedagai Regency and its inhibiting factors. The theory used is communication, resources, disposition and bureaucratic structure. The research method used is descriptive qualitative method by means of observation, interviews and documentation. The results showed that the implementation of the Healthy Indonesia Card Program in Lubuk Saban Village, Pantai Cermin District, Serdang Bedagai Regency has not been effective and has not been on target. The obstacle faced in the Healthy Indonesia Card program was the incomplete data on medicines in the health centers for recipients of the Healthy Indonesia Card. This is not optimal for village officials to communicate with the community when explaining the existence of the KIS program because at the time of gathering the community to socialize only twice a month. And with these inhibiting factors still unable to utilize the potential of natural resources, this study can be concluded that the economy of the underprivileged is helped because they do not think about the costs for medical expenses because they have been registered in the KIS program which has been socialized by the village.